The Symbolic Meaning of Death Ritual in Baduy Society - Romi Romi; Semiarto Aji Purwanto (Tsaqofah, 2022)
This article examines the death rites in the Baduy indigenous people, one of the indigenous peoples in Lebak, South Banten. The Baduy indigenous people have cultural characteristics and beliefs that are unique and different from Banten society in general. The various traditional rituals and socio-religious ceremonies performed by the Baduy community must all refer to the customary norms and rules that apply in the local community; no exception in the death rites. How the Baduy indigenous people interpret death and what symbols are in the death rites of the Baduy indigenous people are two important points that will be examined in this article. In addition, how the symbolic meaning in the death rites of the Baduy indigenous people will also be discussed in this article. This article is the result of field research using ethnographic methods with an anthropological approach. The data collection technique used involved observation, in-depth interviews, documentation and literature study. The death rite is one of the sacred rites in the rite of passage for the Baduy community. They believe that the dead will return to the Mandala Hyang (the place where the souls gather after death) after a 7-day death rite. The various symbols in the Baduy death rites show the continuity and relationship that continues to exist between the living and the dead. The Baduy death rituals have symbols that imply the understanding and meaning of the Baduy people towards death and the dead. For the Baduy people, the relationship between the living and the dead continues until the spirit faces the Holy One.